ChemInform Abstract: Molecular Iodine‐Mediated Domino Reaction for the Synthesis of Benzamides, 2, 2‐Diazidobenzofuran‐3(2H)‐ones and Benzoxazolones. Issue 19 (13th May 2014) - Rajendar, K.; Kant, Ruchir; Narender, T.
Abstract A simple one‐pot protocol allows the conversion of divergent acetophenones and ortho‐hydroxyacetophenones into the title compounds via triiodomethyl ketones as key intermediates.